E-M, an Engineered Endostatin with High ATPase Activity, Inhibits the Recruitment and Alternative Activation of Macrophages in Non-small Cell Lung Cancer - Xu, Min; Zhang, Shaosen; Jia, Lin; Wang, Shan; Liu, Jie; Ma, Xuhui; Wang, Chunying; Fu, Yan; Luo, Yongzhang (Frontiers in Pharmacology, 2017)
Endostatin recently was reported by our laboratory to possess ATPase activity that is indispensable for its anti-angiogenesis and anti-tumor effects. An engineered endostatin, E-M, which owns higher ATPase activity exhibits stronger inhibitory effects on angiogenesis. Tumor-associated macrophages (TAMs), especially M2-polarized TAMs, contribute to tumor progression by promoting tumor cell proliferation, metastasis, angiogenesis, and immunosuppression, thus emerging as crucial targets for therapeutic intervention. Endostatin reportedly modulated functions of TAMs, but the detailed mechanisms remain unclear. Here, in our study, we demonstrated that E-M exhibited stronger inhibitory effects on macrophages than endostatin and other low ATPase mutants, which indicates that the ATPase activity is required for the inhibitory effects of endostatin on TAMs. Moreover, we elucidated that endostatin co-receptor, nucleolin and integrin α5β1, overexpressed on the surface of M2 macrophages, facilitated the internalization of E-M via the caveolae/lipid raft- and clathrin-dependent pathways. E-M inhibited the migration of TAMs through blockade of p38 MAP kinase and Erk1/2 signaling pathways, and prevented the alternative activation of TAMs. As a result, TAM-induced tumor cell proliferation and angiogenic activities in vitro were dramatically suppressed by E-M. In a transplanted non-small cell lung cancer model, E-M remarkably decreased the density of intratumoral macrophages and blood vessels, leading to tumor regression. This study unravels a novel mechanism of endostatin on regulating TAM recruitment and polarization, and suggests that E-M is a remarkably promising and multifunctional anti-tumor agent.